(untitled) (Journal of Nepalese Business Studies, 2024)
Businesses and cooperatives both sectors utilize accounting information for strategic decision-making. Accounting information makes it easy for managers for managerial and operational decision making in cooperatives. The article examines how accounting information affects strategic decision-making in Kirtipur cooperatives. Accounting information plays an important role in sustainable and wise decision-making for cooperatives. The study attempts to provide insightful information on how accounting information influences strategic decisions. Rational strategic decisions can save cooperatives from the present financial and managerial crisis. This research is quantitative and follows a deductive approach. The data is collected field survey based on convenience sampling. SPSS was used to process the raw data that had been gathered. The data has been analyzed and the resultant hypothesis validated using regression analysis, correlation, and descriptive statistics. The data was collected from 60 usable questionnaires returned from respondents. The total population of the study is 96. The first-hand data was gathered using a standardized questionnaire with 5-point Likert scale items. The study indicates that accounting information has played a critical role in strategic decision-making in Kirtipur cooperatives. Because the p-value is 0.000, which is less than 1 percent level of significance. So, the ANOVA table indicates that the model is fitted. There is a significant impact of accounting information on strategic decision-making. Therefore, cooperatives in Nepal can improve managerial and operational decision-making.